Evolution of Precision Agriculture Computing towards Sustainable Oil Palm Industry - K.C. Goh; S.Y. Sim; H.H. Goh; K. Bilal; T.H. Sam; T.Y. Teoh; J. S. Tey (Institute of Advanced Engineering and Science, 2018)
Precision technology elements have not been implemented yet into the sustainable oil palm industry because the knowledge and technology gap. To resolve the gaps, promote sustainability and integrate the technologies, Oil Palm Management System (OPAMS) was introduced. The precision technologies in OPAMS comprises of Geographical Information System (GIS), Global Positioning System (GPS), remote sensing and yield monitoring. A phase by phase System Development Life Cycle (SDLC) methodology was used to generate the said system with feedbacks from oil palm planters as the inputs for OPAMS’s key features. OPAMS ultimately aims to increase the awareness of the industry on the benefits of utilizing technology to improve plantation performances, increase business and environmental sustainability.